Simplified Analytical Methods of Elastic Plates - Takabatake, Hideo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents simplified analytical methodologies for static and dynamic problems concerning various elastic thin plates in the bending state and the potential effects of dead loads on static and dynamic behaviors. The plates considered vary in terms of the plane (e.g. rectangular or circular plane), stiffness of bending, transverse shear and mass. The representative examples include void slabs, plates stiffened with beams, stepped thickness plates, cellular plates and floating plates, in addition to normal plates. The closed-form approximate solutions are presented in connection with a groundbreaking methodology that can easily accommodate discontinuous variations in stiffness and mass with continuous function as for a distribution. The closed-form solutions can be used to determine the size of structural members in the preliminary design stages, and to predict potential problems with building slabs intended for human beings' practical use.
Static and Dynamic Analyses of Rectangular Normal Plates -- Static and Dynamic Analyses of Circular Normal Plates -- Static and Dynamic Analyses of Rectangular Normal Plates with Edge Beams -- Static and Dynamic Analyses of Rectangular Plates with Voids -- Static and Dynamic Analyses of Circular Plates with Voids -- Static and Dynamic Analyses of Rectangular Cellular Plates -- Static and Dynamic Analyses of Circular Cellular Plates -- Static and Dynamic Analyses of Rectangular Plates with Stepped Thickness -- Static and Dynamic Analyses of Rectangular Plates with Stepped Thickness Subjected to Moving Loads -- Static and Dynamic Analyses of Rectangular Floating Plates Subjected to Moving Loads -- Effects of Dead Loads on Static and Dynamic Analyses of Rectangular Plates -- Effects of Dead Loads on Static and Free Vibration Problems of Beams -- Effects of Dead Loads on Dynamic Problems of Beams -- Refined Plate Theory in Bending Problem of Uniform Rectangular Plates.
Keywords: Mechanics, Applied; Solids; Buildings -- Design and construction; Geotechnical engineering; Solid Mechanics; Building Construction and Design; Geotechnical Engineering and Applied Earth Sciences